Basic concepts in nocturia, based on international continence society standards in nocturnal lower urinary tract function. (2nd August 2018) - Hashim, Hashim; Drake, Marcus J.
Abstract : Aims: To review the recommendations on nocturia in the International Continence Society (ICS) Standardization documents, setting out key definitions and parameters for use in clinical practice. Methods: Definitions and evaluations described in the ICS Standards on Nocturia and Terminology for Lower Urinary Tract Function were identified and summarized. Results: The terms have been divided into signs and symptoms. Nocturia as a symptom is waking at night to pass urine and as a sign is the number of times an individual passes urine during their main sleep period. Nocturnal polyuria as a symptom is passing large volumes of urine at night and as a sign is the excessive production of urine during the individual's main sleep period. These should be quantified using a 3‐day bladder diary, thereby facilitating identification of 24‐h polyuria, nocturnal polyuria, lower urinary tract dysfunction, or sleep disorder. Conclusions: The summary reflects the multifactorial influences in nocturia and provides a pragmatic insight into bladder diary analysis for deriving key parameters relevant to clinical therapy.